2011
DOI: 10.1113/jphysiol.2011.207340
|View full text |Cite
|
Sign up to set email alerts
|

State‐dependent changes in astrocyte regulation of extrasynaptic NMDA receptor signalling in neurosecretory neurons

Abstract: Despite the long-established presence of glutamate NMDA receptors at extrasynaptic sites (eNMDARs), their functional roles remain poorly understood. Factors influencing the concentration and time course of glutamate in the extrasynaptic space, such as the topography of the neuronal–glial microenvironment, as well as glial glutamate transporters, are expected to affect eNMDAR-mediated signalling strength. In this study, we used in vitro and in vivo electrophysiological recordings to assess the properties, funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
156
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(182 citation statements)
references
References 64 publications
22
156
2
Order By: Relevance
“…We found that P2 receptor activation by ATP did not induce significant changes in either the frequency, magnitude, or time course of glutamate receptor-mediated sEPSCs, suggesting that ATP did not affect the degree of glutamate release (i.e., no change in PSC frequency) or the magnitude/kinetics of postsynaptic receptors (i.e., no change PSC amplitude/kinetics) in PVN-RVLM neurons. This is different from previous reports in supraoptic nucleus (SON) and PVN magnocellular neurosecretory neurons showing that ATP increased glutamate EPSC frequency and amplitude (Gordon et al 2005;Vavra et al 2011), suggesting that ATP actions in the hypothalamus may be cell type dependent.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…We found that P2 receptor activation by ATP did not induce significant changes in either the frequency, magnitude, or time course of glutamate receptor-mediated sEPSCs, suggesting that ATP did not affect the degree of glutamate release (i.e., no change in PSC frequency) or the magnitude/kinetics of postsynaptic receptors (i.e., no change PSC amplitude/kinetics) in PVN-RVLM neurons. This is different from previous reports in supraoptic nucleus (SON) and PVN magnocellular neurosecretory neurons showing that ATP increased glutamate EPSC frequency and amplitude (Gordon et al 2005;Vavra et al 2011), suggesting that ATP actions in the hypothalamus may be cell type dependent.…”
Section: Discussioncontrasting
confidence: 56%
“…Under basal conditions, however, we found the extrasynaptic glutamate current to be mediated mostly by NMDA (but not AMPA) receptors (Fleming et al 2011;Naskar and Stern 2014;Potapenko et al 2012Potapenko et al , 2013. It is possible, however, that activation of P2 receptors increases extrasynaptic AMPA receptor density and/or glutamate sensitivity, contributing under this condition to glutamate-mediated extrasynaptic actions.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, the origin of the so-called ambient glutamate that allows such tonic activation is still unclear, and little evidence for the source exists, aside from the observation that it is of non-synaptic origin [58,59]. Interestingly, the amplitude of NMDAR-mediated tonic current is strongly enhanced either by blocking glutamate reuptake through the glutamate transporter 1 (GLT1) [58,60], which is predominantly present on glial cells and mediates 95% of glutamate transport, or when slices are challenged with glial toxins [60]. Additionally, a recent study showed that the extent of NMDAR-mediated tonic current depends on glial coverage in the supraoptic nucleus of the hypothalamus [60].…”
Section: Agonist Control Of Nmdar At Extrasynaptic Sitesmentioning
confidence: 99%
“…Interestingly, the amplitude of NMDAR-mediated tonic current is strongly enhanced either by blocking glutamate reuptake through the glutamate transporter 1 (GLT1) [58,60], which is predominantly present on glial cells and mediates 95% of glutamate transport, or when slices are challenged with glial toxins [60]. Additionally, a recent study showed that the extent of NMDAR-mediated tonic current depends on glial coverage in the supraoptic nucleus of the hypothalamus [60]. Hence, the activity of NMDARs that mediate tonic current probably relies on the regulation of extrasynaptic glutamate tone by glia.…”
Section: Agonist Control Of Nmdar At Extrasynaptic Sitesmentioning
confidence: 99%